2022
DOI: 10.1371/journal.pone.0271408
|View full text |Cite
|
Sign up to set email alerts
|

Ginger (Zingiber officinale) extract mediated green synthesis of silver nanoparticles and evaluation of their antioxidant activity and potential catalytic reduction activities with Direct Blue 15 or Direct Orange 26

Abstract: The green synthesis of silver nanoparticles (AgNPs) using a water extract of Ginger (Zingiber officinale) root by microwave irradiation and its antibacterial activities have been reported. However, AgNPs prepared from different parts of ginger root water or ethanol extract by ultrasound synthesis and their antioxidant activity and whether the biogenic could be used to catalyze the reduction of hazardous dye are unknown. This study concentrated on the facile green synthesis of AgNPs prepared from different part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…UV-visible absorption spectra showed a single, prominent broad surface plasmon resonance peak at 420 nm indicating the synthesis of AgNPs (Figure 3). This feature could be attributed to the presence of spherical NPs as indicated in previous studies [18,35]. Yadav et al [38] reported that the plasmon resonance band at 420 nm supported the reduction of AgNO 3 to AgNP.…”
Section: Agnp Synthesis and Characterizationsupporting
confidence: 55%
See 4 more Smart Citations
“…UV-visible absorption spectra showed a single, prominent broad surface plasmon resonance peak at 420 nm indicating the synthesis of AgNPs (Figure 3). This feature could be attributed to the presence of spherical NPs as indicated in previous studies [18,35]. Yadav et al [38] reported that the plasmon resonance band at 420 nm supported the reduction of AgNO 3 to AgNP.…”
Section: Agnp Synthesis and Characterizationsupporting
confidence: 55%
“…AgNPs were prepared from AgNO 3 salt using extracts of the ginger rhizome as reducing and capping agents. Green synthesis of AgNPs from fresh and dried ginger using ethanol and water extracts has been reported as an efficient method by Vijaya et al [33] and Hu et al [18]; it does not require any external surfactants and capping or stabilizing agents since this is achieved by the extract itself. The optimal concentrations of the extract and AgNO 3 (1 mg ginger extract in 1 mL of 1 M AgNO 3 at 80 • C for 6 h) ensured sufficiently low polydispersity index of the AgNPs and pH 6 yielded the highest quantity of nanoparticles.…”
Section: Agnp Synthesis and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations